DEVELOPMENT OF THE LOAD MEASURING DEVICES TO DETERMINE THE RESIDUAL DEFORMATION OF THE ELASTIC SENSING ELEMENT - I. V. Antonets; V. A. Borsoev; R. A. Borisov; S. M. Stepanov (Научный вестник МГТУ ГА, 2018)
The main focus in the design of weighing and batching devices is to create a gravimetric technique, capable of providing not only mass measurement – weighing with the required accuracy and speed, but also automatic control of technological processes and their control and regulation. In this case, the opportunity of two-way communication with a computer when designing the load measuring devices is realized, allowing remote monitoring and solution of logical problems associated with the management process. Modern automatic weighing and batching devices are important parts of comprehensive automation in different branches of industry. Existing developments of electrical, electronic, computing and other branches of instrument engineering techniques allow to implement transformations of the measured quantity with a very high degree of accuracy. However, if the measured quantity in the weighing process is perceived by the elastic sensing element of low quality, then no matter how high the accuracy of further changes is; the characteristics of the elastic element will limit the accuracy of the instrument as a whole. Although the elastic elements are simple mechanical parts, and many types of elastic elements are known and are widely used for many decades, their performance often does not meet the requirements, and hampers the device creation of high accuracy classes. Growing requirements for primary transformer makes actual the problem solution of improving the quality of elastic sensing elements not only in the manufacture but in the design. This led to the appearance of projects aimed at the development of computational and experimental methods that have altered the methodology for the design of force measuring devices.